Production Risk and Management Strategies of Potato Farming in Nagari Alahan Panjang, Solok Regency, West Sumatera - Yusmarni Yusmarni; Rabi’atul Adawiyah; Nofialdi Nofialdi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Solok Regency is the largest potato-producing area in West Sumatra. However, from 2015 until 2020, potato production in Solok Regency has experienced a decline. The decline in potato production in Solok Regency indicates production risks in potato farming. The decrease in potato production could be caused by several factors related to potato farming, such as rainfall, pests, diseases, and others. This study aims to identify and assess the sources of production risks in potato farming and analyze risk management in managing production risks in potato farming in Nagari Alahan Panjang, Solok Regency. Data were collected from 31 potato farmers in Nagari Alahan Panjang, the village with the highest potato production in Solok Regency. This study used a risk mapping matrix to analyze the data. The results of the study found nine sources of production risk in potato farming, namely: poor seeds, high rainfall, expensive fertilizers, unproperly weeding, caterpillar pests, thrips pests, pig pests, fusarium wilt disease, and phytophthora disease. This study formulates two types of risk management: preventive and mitigation strategies. A preventive approach is to prevent or reduce the frequency of risk by rotating crops properly and using organic fertilizers. A mitigation strategy is to minimize the impact of production risks by diversifying crops, utilizing biological agents of Trichoderma sp, applying proper Weeding, and partnering with certified potato seed breeders to get good quality seed.